Pendampingan Kewirausahaan Mahasiswa pada Jasa Katering Dapur Alifa - Arninda, Arninda; Alya Supandih, Fathia; Utari, Melia; Kusuma, Haniyyah (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
The entrepreneurship mentoring program for Dapur Alifa effectively integrates theory and practice, significantly enhancing various business aspects. Beginning with a SWOT analysis, the program identified key strengths, weaknesses, opportunities, and threats, forming the foundation for tailored strategies. Operational efficiency improved by 25% through better resource management and team organization, enabling Dapur Alifa to handle growing customer demands. The implementation of a 7P-based marketing strategy, supported by digital promotion, increased customer acquisition by 35%, demonstrating the importance of digital platforms in expanding market reach. Ensuring business legality through certifications, such as NIB and halal certification, enhanced consumer trust and opened access to premium markets. Practical activities, including market research, promotional campaigns, and participation in the EA VIII 2024 in Jambi, resulted in a 30% growth in catering orders within three months. The program also fostered innovation by encouraging healthier, budget-friendly menu development, maintaining competitiveness in a dynamic market. This mentoring initiative highlights the critical role of guidance in equipping students with entrepreneurial skills, fostering innovation, and driving sustainable growth for Micro, Small, and Medium Enterprises (MSMEs). Dapur Alifa serves as a model for similar enterprises, contributing to community empowerment and aligning with broader economic development goals.